Retroperitoneal extramedullary hematopoietic pseudotumor in ataxia–telangiectasia - Sean James Judge; Trevor A Plescia; Cyrus P Bateni; Morgan A Darrow; Christopher P Evans; Robert J Canter (Rare Tumors, 2018)
Ataxia–telangiectasia confers a significant increase in the development of several cancer types, most commonly leukemia and lymphoma. However, as the natural history for these patients is evolving and their lifespan is increasing, there is the potential for the development of additional uncommon tumors in an already rare patient population. We report the first case, to our knowledge, of an incidental retroperitoneal tumor in a 26-year-old woman undergoing evaluation for hepatic dysfunction. The mass was suspicious for retroperitoneal sarcoma, but proved to be an extramedullary hematopoietic pseudotumor after extensive pathologic evaluation. The changing landscape of neoplasms associated with ataxia–telangiectasia is discussed with emphasis on previously underreported benign and malignant tumors.